Monetary policy in Western Balkan countries and its impact on the economy - Gruikj, Vesna (2019)
The thesis focuses on analyzing the monetary policy in the Western Balkan countries, and how the monetary policy impacts the economy in the particular country through its monetary policy instruments. The countries being observed are: Albania, Bosnia and Herzegovina, Croatia, Macedonia, and Serbia.